ABU BATUBARA SEBUAH KONSEP INOVATIF BAGI PRODUKSI BATA ABU ABU UNTUK MEMPEROLEH KEKUATAN TINGGI DAN AMAN TERHADAP LINGKUNGAN (A Literatur Study) - Eisenring, Maryo Pitanda (MEKTEK, 2013)
Several experiments have been conducted by using Fly Ash and some similar materials, such as lime, sand, gypsum, quarry dust, Fibre Glass for Bricks-making, which generally aims to get a high-strength brick, and safe for the environment. Fly Ash classified as a B-3 waste is a coal combustion residue generated from burning coal in Steam power plant. Because Fly Ash contains SiO2, Al2O3,P2O5 and Fe2O3, the levels are quite high; the nature of its cement characteristic (pozzolonic) is very good for the use of construction industry. In this paper Fal-G brick production process, uses of rap-trap bond in Fal-G brick masonry prism test study and from the economic point of view it turns out the use of hollow block Fal-G can saveconstruction costs 20 to 30 %. Observations, limitations and suggestions from the various regions have been described.Keywords: Fly ash, rattrap bond, prism test, environment, infrastructure, economy.